Folic acid supplementation during pregnancy modulates hepatic methyl metabolism and genes expression profile of neonatal lambs of different litter sizes. Issue 1 (14th July 2022) - Wang, Bo; Jian, Luyang; Li, Heqiong; Li, Zhen; Luo, Hailing; Gao, Yuefeng
Abstract: Maternal folic acid (FA) plays an important role in the fetus development, but it is unknown the response of hepatic metabolism in the offspring from different litter sizes to maternal FA supplementation. In the present study, this was done by feeding the ewes with 0, 16 and 32 mg/(kg·DM) FA supplemented diet during pregnancy and analysing the hepatic one-carbon metabolism-related indices and gene expression in the neonatal lambs of different litter sizes (twins, TW; triplets, TR). Regardless of litter sizes, the concentrations of folate, methionine, S-adenosylmethionine and DNA methyltransferase increased significantly, but homocysteine and S-adenosylhomocysteine decreased in the liver of newborn lambs from ewes whose diet was supplemented with FA. In TW, maternal FA status has little effect on hepatic genes expression profile of newborn lambs, and no significant enriched pathway was found. However, DEG involved in cell proliferation such as CCNA2, CCNB2, CCNE2, CDK1 and BUB1 were significantly enriched when the ewes were supplemented with FA in TR groups. In addition, nucleotide synthesis-related genes such as POLD1, POLD2, MCM4 and MCM5 were enriched markedly in DNA replication and pyrimidine metabolism pathways in triplets when a higher FA ingestion [32 mg/(kg·DM)] was implemented in ewes. This finding demonstrated that the hepatic methyl metabolism in TW and TR newborn lambs was regulated by maternal FA status. The hepatic cell proliferation and nucleotide metabolism related genes in TR were more susceptible to maternal dietary FA supplementation during pregnancy.